C3 – Carbon Concrete Composite – Vom größten Bauforschungsprojekt zum bedeutendsten Verband für Carbonbetonbau. (27th December 2022) - Kranich, Sandra; Schladitz, Frank
Abstract: Carbonbeton findet zunehmend Anwendung in der Praxis: im Neubau und im Bereich der Sanierung. Zahlreiche Unternehmen, Verbände und Institutionen arbeiten unter der Dachmarke von C 3 – Carbon Concrete Composite daran, den Einsatz der Carbonbetontechnologie zu erleichtern, die zahlreichen Vorteile von Carbonbeton zu nutzen und somit einen wesentlichen Beitrag zur Klimaneutralität zu leisten. Dieser Aufsatz beschreibt die Anfänge der in den 1990er‐Jahren abwegig klingenden Idee und skizziert die Entwicklungsphasen von einem Bauforschungsprojekt zum bedeutendsten Verband auf dem Gebiet des Bauens mit Carbonbeton. Abstract: C 3 – Carbon Concrete Composite – From the largest construction research project to the most important association for carbon reinforced concrete construction. Carbon reinforced concrete is becoming increasingly used in practice: in new construction and in the field of retrofitting. Numerous companies, associations and institutions are working under the brand of C 3 – Carbon Concrete Composite to make the use of carbon reinforced concrete technology easier, to exploit the numerous advantages of carbon reinforced concrete and thus to make a significant contribution to climate neutrality. This article describes the beginnings of the idea, which sounded absurd in the 1990s, and outlines the development phases from a construction research project to the most important association in the field of building with carbon reinforced concrete.